Palladium Mesoionic Carbene Pre-catalyst for General Cross-Coupling Transformations in Deep Eutectic Solvents - Marset, Xavier; Saavedra, Beatriz; González-Gallardo, Nerea; Beaton, Alexander; León, Martín M.; Luna, Raúl; Ramón, Diego J.; Guillena, Gabriela (Frontiers in Chemistry, 2019)
A strong -donor mesoionic carbene ligand has been synthesized and applied to four different palladium-catalyzed cross-coupling transformations, proving the catalyst/medium compatibility and the increased activity of this system over previous reports in Deep Eutectic Solvent medium. Some cross-coupling processes could be carried out at room temperature and using aryl chlorides as starting materials. The possible implementation of multistep synthesis in eutectic mixtures has also been explored. The presence of palladium nanoparticles in the reaction media has been evaluated and correlated to the observed activity